Efisiensi Inhibisi Korosi Baja Lunak dalam Media Asam dengan Inhibitor Ekstrak Kulit Buah Kakao (Theobroma cacao) - Yetri, Yuli; Emriadi, E; Jamarun, Novesar; Gunawarman, G (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2016)
Inhibition and adsorption properties of Theobroma cacao peel polar extract addition on corrosion inhibition efficiency of 0.3%C mild steel in hydrochloric acid solution for various exposuring time, extract concentration and working temperature were investigated using weight loss test method. Electrochemical polarization test was also conducted to confirm the effectiveness of inhibition. Infrared spectrum of the samples was also evaluated to reveal compounds of the extract which controll the inhibition process. Morphology and local composition of sample surfaces were respectively examined by scanning electron microscope (SEM) and energy dispersive X-ray spectroscopy (EDX). Thermodynamic parameters such as energy activation, enthalpy, entropy and change in the free energy were then determined using related data. The results show that the inhibition efficiency increases significantly up to 96.3% (by weight loss method) and 92.08% (Tafel) with the increase of TCPE content. The optimum efficiency is obtained at extract concentration of 2,5% for exposuring time of 768h. However, the efficiency decreases slightly with increasing working temperature in the range of 303K-323K. The polarization curve shows the inhibitor behaves as a mixed inhibitor with the dominant cathodic inhibition. The adsorption model is found to obey Langmuir adsorption isotherm. Surface condition is improved due to the adsorption and then formation of thin layer film protection in the surface of the steel. The addition of extract of cacao peels into HCl is effective to minimize corrosion attack on the mild steel.